Prevalence and diversity of Escherichia coli isolated from a barley trial supplemented with bulky organic soil amendments: green compost and bovine slurry. (1st March 2014) - Holden, N.J.; Wright, F.; MacKenzie, K.; Marshall, J.; Mitchell, S.; Mahajan, A.; Wheatley, R.; Daniell, T.J.
Abstract: A barley field trial supplemented with bulky organic soil amendments, municipal compost or bovine slurry was sampled for Escherichia coli to test the hypothesis that E. coli isolated from the soil or from barley plants were derived from bovine slurry. A qualitative analysis showed that a total of 12% of the bulk soil cores and 16% of harvested grain samples yielded E. coli . The strongest association for positive detection of E. coli from soil was with time of year and for slurry‐treated plots, with irrigation. However, E. coli were detected in plots from all treatment types and not exclusively associated with bovine slurry. Phylogroup, plasmid profiling and population genetics analysis (multilocus sequence typing) revealed extensive genetic diversity. Identical sequence types for slurry and soil isolates were detected, indicative of direct transfer into the soil, although not frequently. Host interaction assays with selected isolates showed a variation in the ability to colonize barley roots, but not in interactions with bovine cells. The work has implications in appropriate use of E. coli as a faecal indicator as isolates were widespread and diverse, reinforcing the view that some are a natural part of the microflora in agricultural systems. Significance and Impact of the Study: Faecal deposition is considered to be the main process that introduces Escherichia coli into soil, giving rise to their use as a faecal indication species and the potential for cycling pathogens in agricultural systems. We found that bovine slurry was not the main source of E. coli in a barley trial and a high degree of diversity was present in the collection. The findings support the hypothesis that the population structure of E. coli in secondary habitats is shaped by the environment and highlight the drawbacks of its use as a faecal indicator species.